THE EFFECT OF BRAINSTORMING TEACHING TECHNIQUE ON STUDENT’S ACHIEVEMENT IN WRITING ANALYTICAL EXPOSITION TEXT AT THE SECOND GRADE OF SMA NEGERI 1 LINTONG NIHUTA - Andreas Theofilus Hutasuhut; Lamria Purba; Romsina Siregar (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2023)
This study focuses on knowing the effect brainstorming teaching technique in writing analytical exposition text at the Second grade of SMA Negeri 1 Lintong Nihuta. This research was conducted with an experimental quantitative design. The population of this study were students of class XI SMA Negeri 1 Lintong Nihuta . In this study the researchers took two classes as samples. They were 20 students in the experimental class and 20 students in the control class. Data collection techniques are tests and documentation. The researcher used the T-test statistical calculation to analyze the data. The tests used were pre-test and post-test for both classes. The results showed that the average pretest value of the experimental class was 51,8. Meanwhile, the control class was 40,00. while the post-test average value of the experimental class was 78. Meanwhile, the control class was 45,9. That is, the average post-test score of the experimental class was higher than that of the control class. The results of the t-test calculation show that the t-test value is higher than the t-table value. The t test value is 17,387 while the t-table value with db:38 which is included in the db=40 category is 2.21. This means that there is a significant the effect of brainstorming technique in writing Analytical exposition Text So, Ha is accepted and Ho is rejected.